(untitled) (مجلة البحوث الأكاديمية, 2023)
This paper investigated the major causes of speaking anxiety and students’ perceptions in a Libyan EFL context. Fourth semester students (N=30) of English at Misurata University participated in the study, in the academic year 2022-2023. The data of the level of EFL speaking anxiety were collected through a questionnaire, and then, other participants (N=7) were interviewed to get in-depth data on speaking anxiety. The quantitative data were analysed through descriptive statistics, and the qualitative data were analysed via content analysis. The results of the quantitative data revealed that the majority of the students (70%) experienced a high level of EFL speaking anxiety. The qualitative data, on the other hand, showed that there were mainly three factors behind students’ speaking anxiety namely linguistic, individual and gender-related factors, and most students perceived the speaking skill as an anxiety provoking factor. Finally, depending on the findings of the study, some recommendations were emphasized.